The Application of Modern Methods in Teaching Anatomy in Medical Colleges - Mukhamadaliev Asadbek Yo'ldashali o'g'li (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
Anatomy, being a fundamental subject in the medical education curriculum, requires innovative teaching approaches to engage students and ensure effective learning. This article explores the application of modern teaching methods in the anatomy education of students at medical technical schools. It discusses various contemporary teaching strategies, such as interactive learning, digital tools, and virtual reality, which can enhance the understanding of complex anatomical structures. The study emphasizes the importance of integrating these modern techniques with traditional methods to create a more engaging and efficient learning environment. Furthermore, it examines the benefits of these innovative approaches, including increased student participation, improved retention, and the ability to visualize anatomical structures in 3D. The article concludes by recommending the adoption of a blended learning approach that combines technology with conventional teaching methods to improve anatomy education in medical colleges.